Answer:
The line equation in the slope-intercept form:
[tex]y=\frac{3}{2}x+2[/tex]
Step-by-step explanation:
We know that the slope-intercept of line equation is
[tex]y = mx+b[/tex]
Where m is the slope and b is the y-intercept
Given the line
[tex]2x + 3y = 9[/tex]
Writing in the slope-intercept form
[tex]2x + 3y = 9[/tex]
[tex]y=-\frac{2}{3}x+3[/tex]
Therefore, the slope of the line = m = -2/3
We know that a line perpendicular to another line contains a slope that is the negative reciprocal of the slope of the other line, such as:
slope = m = -2/3
perpendicular slope = – 1/m
[tex]=-\frac{1}{-\frac{2}{3}}=\frac{3}{2}[/tex]
Given the point
(x₁, y₁) = (-2, -1)
Using the point-slope form of the line equation
[tex]y-y_1=m\left(x-x_1\right)[/tex]
where m is the slope and (x₁, y₁) is the point
substituting the perpendicular slope m = 3/2 and the point (-2, -1)
[tex]y-\left(-1\right)=\frac{3}{2}\left(x-\left(-2\right)\right)[/tex]
Writing in the slope-intercept form
[tex]y+1=\frac{3}{2}\left(x+2\right)[/tex]
subtract 1 from both sides
[tex]y+1-1=\frac{3}{2}\left(x+2\right)-1[/tex]
[tex]y=\frac{3}{2}x+2[/tex]
Thus, the line equation in the slope-intercept form:
[tex]y=\frac{3}{2}x+2[/tex]